Jack Bean (Canavalia ensiformis) Meal Inclusion and Lactic Acid Bacteria Supplementation on the Performance of IPB D1 Chickens - Sakinah, Raudoh Gholia; Hermana, Widya; Nahrowi, Nahrowi; Ridla, Muhammad (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2024)
This study investigates the effects of including jack bean (Canavalia ensiformis) meal in the ration and lactic acid bacteria (LAB) supplementation on the performance and carcass yield of IPB D1 chickens. Jack bean meal (JBM) contains a high-energy, protein-rich feed ingredient that can substitute soybean meal, though it contains antinutrients such as hydrocyanic acid. Pre-treating jack beans through soaking and peeling reduces these antinutrients, allowing JBM to replace up to 20% of the diet. The inclusion of exogenous enzymes like protease can further enhance nutrient absorption and broiler health. The study involved 240 IPB D1 chickens, divided into four groups: control feed without LAB (J0L0), control feed with LAB (J0L1), treatment feed without LAB (J1L0), and treatment feed with LAB (J1L1). Feed intake, body weight gain (BWG), and feed conversion ratio (FCR) were measured weekly from weeks 3 to 9, and carcass yields were evaluated at the end of the study. Results showed significant variations (p<0.05) in weekly feed intake, BWG, and FCR across the treatments. Chickens fed JBM had lower (p<0.05) feed intake and BWG but these improved with LAB supplementation. FCR values improved significantly (p<0.05) with LAB supplementation in both control and treatment feeds. Carcass yield analysis indicated that LAB supplementation led to higher (p<0.05) final body weight and carcass yield, while JBM inclusion resulted in lower values (p<0.05). The study concludes that while JBM can negatively affect chicken performance due to antinutrients, LAB supplementation can mitigate these effects, enhancing both performance and carcass yield. In addition, probiotics are beneficial in poultry diets, counteracting antinutritional factors in feed ingredients like Jack bean meal. Key words: antinutrient, chicken health, probiotic, soybean meal